Project- and Research-Based Teaching in Civil Engineering - Bartels, Niels; Stolz, Katrin (International Journal of Engineering Pedagogy (iJEP), 2024)
Research-based practical applications are becoming increasingly important in providing valuable solutions to the challenges facing the construction industry. In this paper, we present a teaching concept that was implemented and evaluated in four courses, addressing the development of future-proof academic skills, particularly scientific working skills, in the field of civil engineering. The first evaluation results from a survey among the students who participated in the four courses are presented on the extent to which project-based and researchbased learning promote domain competences, planning, and study skills. The results indicate that, especially in master’s degree courses, future skills are improved by paper-based learning. Additionally, student motivation increases due to the boost in creativity and group work facilitated by the teaching concept. On the other hand, the results suggest that guidelines are necessary to implement paper-based learning, especially in bachelor’s degree courses. Furthermore, it is crucial that future-proof academic skills are relevant for success in the practical working context.